2012 IEEE Congress on Evolutionary Computation 2012
DOI: 10.1109/cec.2012.6252956
|View full text |Cite
|
Sign up to set email alerts
|

Fast shortest path optimization inspired by shuttle streaming of Physarum polycephalum

Abstract: The plasmodium of the slime mold Physarum polycephalum, a large amoeboid organism, displays remarkable intelligent behaviors such as solving mazes, shuttle streaming and event anticipation. These amoeboid behaviors are results of the dynamics of the viscoelastic protoplasm and its biochemical rhythms. Having inspired by the intelligence shown by this primitive organism without a nerve system to solve mazes, we proposed mathematical models to mimic the intelligent foraging behavior that can be used to find the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We shall next describe the shuttle-streaming model following [11]. This model is based on three biological observations about P. polycephalum : open-ended tubes gradually disappear;when two tubes connect the same food sources, the longer one disappears;outside changes such as the addition of nutrients can cause changes to the rhythmic contractions and shuttle streaming of Physarum . Shuttle streaming is the flow of protoplasm through Physarum ’s tubes and plays an important role in chemical signalling.…”
Section: Modelling Physarum Polycephalummentioning
confidence: 99%
See 2 more Smart Citations
“…We shall next describe the shuttle-streaming model following [11]. This model is based on three biological observations about P. polycephalum : open-ended tubes gradually disappear;when two tubes connect the same food sources, the longer one disappears;outside changes such as the addition of nutrients can cause changes to the rhythmic contractions and shuttle streaming of Physarum . Shuttle streaming is the flow of protoplasm through Physarum ’s tubes and plays an important role in chemical signalling.…”
Section: Modelling Physarum Polycephalummentioning
confidence: 99%
“…Physarum has also been shown to be able to share information and fuse with other Physarum organisms [7]. Recently, several mathematical models inspired by Physarum have been developed to approach problems such as the shortest path or Steiner tree problems [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have shown that Physarum Polycephalum in this plasmodium state is able to solve mazes, find the shortest path, build highquality networks between multiple points, adapt and respond to stimulus, and also remember past events [2,12,17]. Recently, several mathematical models inspired by Physarum have been developed to approach problems such as the shortest path or Steiner tree problems [3,4,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…We shall begin this paper by introducing in Section II some of the different models used in the literature to study Physarum Polycephalum, paying particular attention to the flow-conductivity model [3], the cellular model [4], the multi-agent model [7], and the shuttle-streaming model [14].…”
Section: Introductionmentioning
confidence: 99%